Molecular characterization of 16S rRNA and internal transcribed spacer (ITS) regions of Aeromonas spp. isolated from cultured freshwater fishes in Malaysia - K.P., Diyana Nadhirah; Md Yasin, Ina Salwany (Excellent Publishers, 2016)
The Aeromonas spp., which are found mostly in freshwater fishes are known to cause uncontrolled disease outbreak in aquaculture system. In the present study, twenty-two of Aeromonas spp. strains isolated from diseased freshwater fishes were identified using the 16S ribosomal RNA (rRNA) and internal transcribed spacer (ITS) regions gene amplification where they produced a 1500 bp and 1000-1200 bp amplicon each. Phylogenetic analysis with BLASTn and 16S rRNA neighbor-joining bootstrapping methods revealed that all strains were identified up to genus level with 15 strains were classified as Aeromonas hydrophila (A. hydrophila) and the rest were Aeromonas veronii (A. veronii). Further ITS gene analysis disclosed strains identification up to species level; A. hydrophila (14 strains) and A. veronii (8 strains). These rapid DNA-based detection methods are simple, easy to perform and faster in identifying Aeromonas spp., thus are absolutely efficient for regular monitoring of Aeromonas spp. in a potential outbreak situation.